The effectiveness of rumination-focused cognitive-behavioral therapy on interpretation bias and social isolation in adolescent girls with social anxiety disorder - Alboushoke, Seyede Fazileh; Safarzadeh, Sahar; Hafezi, Fariba; Ehteshamzadeh, Parvin (Researcher Bulletin of Medical Sciences, 2025)
Objective: Social anxiety disorder, one of the most chronic and prevalent anxiety disorders, is often referred to as a "hidden disorder" and can significantly impair both occupational and social functioning. This study aimed to determine the efficacy of rumination-focused cognitive-behavioral therapy (RFCBT) in reducing interpretation bias and social isolation among adolescent girls with social anxiety disorder. Materials and Methods: This study employed a quasi-experimental pre-test, post-test, and follow-up design. The population of the study consisted of all female high school students diagnosed with social anxiety disorder in Ramashir in 2023. A sample of 25 participants was selected using purposive sampling based on the inclusion criteria. Participants completed the interpretation bias and social isolation questionnaires at pre-test, post-test, and follow-up stages. The experimental group received 10 sessions of 90-minute RFCBT. Data analysis was conducted using repeated measures analysis of variance. Results: The results indicated that RFCBT led to a significant reduction in interpretation bias and social isolation at post-test (P<0.001). This effect was maintained at follow-up, demonstrating the durability of RFCBT. Conclusion: RFCBT is an effective treatment for social anxiety disorder in adolescent girls. This suggests that RFCBT is a valuable tool for helping individuals with social anxiety disorder overcome cognitive distortions and improve their social functioning. However, more research is needed to determine if these findings apply to different populations and to identify factors that might influence treatment outcomes.